2011
DOI: 10.1007/s00170-011-3729-0
|View full text |Cite
|
Sign up to set email alerts
|

Compliant assembly tolerance analysis: guidelines to formalize the resistance spot welding plasticity effects

Abstract: The variational analysis of compliant assemblies is mainly based on linear elastic models. Some guidelines have been defined to integrate material plasticity into a tolerance analysis model in order to improve its results when considering the resistance spot welding (RSW) process. A finite element model that simulates the body-in-white and RSW processes has been applied to butt and slip joints, with parts subjected to dimensional and geometrical tolerances that cause gap mismatching condition and loading inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…At the same time, the finite element method (FEM) was also applied in the tolerance analysis. For example, Liu and Hu (1997) developed the method of influence coefficient (MIC) to simulate compliant sheet metal assemblies, Chang and Grssard (1997) proposed PCFR (Positioning, Clamping, Fastening and Releasing) cycle to model the assembly of compliant parts, butt joint and a slip joint in a body in white (BIW) process are analyzed in the work of Moos and Vezzetti (2012). However, the conventional statistical tolerance simulation results has a shortage in fitting to the real manufacturing processes.…”
Section: Tolerance Analysis In Automobile Processesmentioning
confidence: 99%
“…At the same time, the finite element method (FEM) was also applied in the tolerance analysis. For example, Liu and Hu (1997) developed the method of influence coefficient (MIC) to simulate compliant sheet metal assemblies, Chang and Grssard (1997) proposed PCFR (Positioning, Clamping, Fastening and Releasing) cycle to model the assembly of compliant parts, butt joint and a slip joint in a body in white (BIW) process are analyzed in the work of Moos and Vezzetti (2012). However, the conventional statistical tolerance simulation results has a shortage in fitting to the real manufacturing processes.…”
Section: Tolerance Analysis In Automobile Processesmentioning
confidence: 99%
“…As a further description of the result in [9], for a butt joint with a tolerance interference condition that hinders the correct loading on fixture, in figure 1 have been reproduced the total elastic strain energy density field after the clamps and the electrodes closure (fig. 1a), after the thermal cycle (fig.…”
Section: Introductionmentioning
confidence: 95%
“…The previous work of Moos et al [9] showed that, starting from welding flanges which are subjected to tolerances, the weldgun closure can cause relative sliding motion between the two flanges that are made permanent by the weld spot and that the deformations imposed by fixtures and electrodes before the weld cycle, also cause plasticization away from the welding spot, near bending fillets and locators. The comparison of the spingback of a butt joint calculated with the same boundary conditions, changing only the material model form elastic to plastic, also showed completely different behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of these spot welds is to lock the geometry when the parts are being released from the fixture. The sequence in which these points are being set has a significant effect on the final geometrical outcome [3]. In Fig.…”
Section: Introductionmentioning
confidence: 99%